Comparing the vision quality using double-pass technique in eyes with corrected refractive errors and emmetropic eyes - Henriquez,Maria A. (2022)
ABSTRACT Purpose: To evaluate the vision quality by measuring the objective light scatter index and objective optical quality parameters (Strehl Ratio and Modulation Transfer Function) in patients with emmetropia and ametropia. Methods: This prospective, cross-sectional study included 408 eyes. The ametropic group comprised of eyes with best-corrected visual acuity of 0.0 logMAR or better and present at least a refractive error of ≥0.25 D. Patients underwent slit lamp examination, visual acuity, refraction, and vision quality using the HD Analyzer. Results: The mean objective light scatter indices were 0.62 ± 0.63, 0.77 ± 0.70, 0.74 ± 0.30, 0.93 ± 0.55, and 0.85 ± 0.61, and mean Strehl Ratio and Modulation Transfer Function scores were 38.17 ± 10.4, 37.37 ± 10.06, 29.84 ± 9.71, 33.2 ± 12.11, and 33.13 ± 10.09 in emmetropes, myopia, hyperopia, spherical equivalent of ≥0, and spherical equivalent of <0, respectively. Differences in all variables were significant between emmetropic and corrected hyperopic and between spherical equivalent of ≥0, and spherical equivalent of <0 eyes (p<0.05). Conclusion: In spectacle-corrected conditions (with trial frames), emmetropic and simple myopic eyes had significantly better vision quality compared to hyperopic and astigmatic eyes. The clinical significance of these results should be investigated in further studies.